Determinación de la composición química, propiedades físicas y evaluación de la actividad biológica del aceite esencial de Piper lanceifolium de la provincia de Zamora Chinchipe - Palacio Jaramillo, Carlos Eduardo (2015)
This research is considered very important because it shows the study of the essential oil of Piper lanceifolium that crese is a shrub in the warm zone, the essential oil of the aerial parts was extracted by hydrodistillation. The chemical composition of the essential oil was determined by gas chromatography-mass spectrometry GC / MS and the flame ionization detector GC / FID. The biological activity was evaluated by the broth microdilution method and antioxidant activity. Oil physical properties were also determined. Identified compounds that comprise 93% of the oil. The major components were safrole (41,23%), dill apiole (13,06%) The density of the essential oil of Piper lanceifolium was 1.03 and the refractive index was 1.52. The oil showed good biological activity against Klebsiellapneumoniae (LT2) especially before (CMI 500μg/mL).